dx

Homework Helper

Gold Member

- 2,003

- 18

## Main Question or Discussion Point

Consider the following situation :

There are three variables A, B and C. (and i,j,k are constants )

Keeping C constant, and varying the other two, you find that

A = kB ------(1)

Now, Keeping B constant, and varying the other two, you find that

A = iC ------(2)

I know that it follows from these two observations that

A = jBC

But I am not sure how we can algebraically deduce this from the equations (1) and (2).

We get [tex] A^2 = ikBC [/tex]

Presumably, [tex] ik = \sqrt{j}BC [/tex]

But how do we deduce this?

There are three variables A, B and C. (and i,j,k are constants )

Keeping C constant, and varying the other two, you find that

A = kB ------(1)

Now, Keeping B constant, and varying the other two, you find that

A = iC ------(2)

I know that it follows from these two observations that

A = jBC

But I am not sure how we can algebraically deduce this from the equations (1) and (2).

We get [tex] A^2 = ikBC [/tex]

Presumably, [tex] ik = \sqrt{j}BC [/tex]

But how do we deduce this?